Performing Ocular Examinations as A Component of Self-Care For Individuals with Leprosy with The Aim of Eradicating Social Stigma and Prejudice - Hendriati Hendriati; Tutty Ariani; Havriza Vitresia; Kemala Sayuti; Andrini Ariesti; Julita Julita; Qaira Anum; Satya Wydya Yenny; Rina Gustia; Gardenia Akhyar; Ennesta Asri; Indah Indria Sari; Astria Rima Rara Yuswir; Novian Novian; Rizki Dwayana; Agustin Vira; Rika Desviorita; Rendra Darma Satria (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
Leprosy is still a health problem in several countries, including Indonesia. Disability due to leprosy is a health threat for sufferers and causes quality-of-life problems that can disrupt the productivity of leprosy patients. Ocular involvement in leprosy is joint, but little data has been reported. Apart from multi-drug treatment (MDT), leprosy sufferers must also be able to carry out continuous self-care to prevent further disability. This is a collaborative activity between the Department of Ophthalmology and Dermatology Venereology of the Faculty of Medicine, the University of Andalas in Puskesmas Pauh Kamba district of Padang Pariaman. This is an advocacy activity on self-care (3M: Seeing, Examining, and Protecting) and eye examination. The activity was followed by interactive discussions and continued with a direct examination for skin abnormalities and disabilities, eye examination, and fundoscope. The activity results were obtained from 24 respondents, 11 men and 13 women. The age range is 16-59 years (67%), with the highest level of education being Elementry School graduates, which is 11 people (46%). In the self-care questionnaire of patients, 40% behaved well, and the results of eye examinations almost suffered from dry eye complaints without disabilities.